The Role of Strategic Approaches in Planning and Development of Educational Institutions - Baidowi, Ahmad; Dewi, Erni Ratna (PT. Anagata Sembagi Education, 2025)
This study aims to gain a deeper understanding of how strategic approaches play a role in the planning and development process of educational institutions, particularly in improving management effectiveness, service quality, and institutional competitiveness. The research method used was a qualitative case study approach, involving institutional leaders, educators, and managerial staff as key informants. Data were collected through in-depth interviews, participant observation, and institutional document review. Data were then analyzed using data reduction, data presentation, and thematic conclusion drawing techniques. The results indicate that the implementation of a strategic approach has a significant influence on the direction and sustainability of educational institutions, particularly in terms of establishing a vision and mission, managing resources, and improving program quality. However, this study also found a gap between strategy planning and implementation, caused by limited human resources, a weak evaluation system, and suboptimal organizational communication. Overall, these findings confirm that the success of educational institution development is highly dependent on the consistent implementation of strategies oriented towards quality, innovation, and adaptation to changes in the educational environment.